Modified nano silicon dioxide continuously-mixed fracturing fluid as well as preparation and use thereof

Through the combination of nano-silica with controllable hydrophobicity and polymer compounds such as polyacrylamide, a modified nano-silica continuous mixing fracturing liquid is formed, which solves the problems of long liquid dispersion time and poor dispersion in the prior art. , achieves rapid swelling and efficient fracturing effects, reducing labor intensity and pollution risks.

CN119307246APending Publication Date: 2025-01-14CHINA NAT PETROLEUM CORP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310860362.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-13
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

In the fracturing transformation of dense reservoirs, the conventional fracturing fluid has a long liquid distribution time, high labor intensity, residual liquid pollutes the environment and has low automation, and cannot meet the efficient needs of factory construction, especially nano-dioxide. Silicon has poor dispersion in the oil phase, which affects the fracturing effect.

Method used

Using nano-silicon dioxide with controllable hydrophobicity as the suspension agent, the surface modification treatment makes it have good dispersion in the oil phase, and it is combined with polymer compounds such as polyacrylamide to form modified nano-silicon dioxide continuously. Mix the fracturing liquid, use base oil as solvent, and achieve rapid dispersion and stable suspension through stirring and ultrasonic dispersion technology.

Benefits of technology

The rapid swelling and ready-to-use fracturing fluid system has been achieved, reducing the liquid dispensing time, improving the degree of automation, reducing labor intensity, and avoiding residual liquid pollution, improving the stability of oil-phase dispersed polymer compounds and Fracturing effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of oilfield chemistry, in particular to a modified nano-silica continuously-mixed fracturing fluid and a preparation and use method thereof, the modified nano-silica continuously-mixed fracturing fluid comprises the following raw materials in percentage by mass: 2-6% of hydrophobicity-controllable nano-silica, 0.5-1.2% of a surface treating agent, 30-48% of polyacrylamide and 44.8-67.5% of base oil. The invention provides a modified nano silicon dioxide continuously-mixed fracturing fluid which has the characteristics of low damage and continuous mixing, is convenient to prepare and use, can effectively improve the stability of an oil-phase dispersed high-molecular compound system, realizes rapid swelling of the fracturing fluid system, can be used when being prepared, and has the advantages of high safety and high efficiency. The liquid preparation time in the fracturing operation can be shortened, the automation degree is improved, the labor intensity is reduced, and residual liquid pollution is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oilfield chemistry and relates to a modified nano-silicon dioxide continuously mixed fracturing fluid and a preparation and use method thereof. Background Art

[0002] The fracturing and transformation of tight reservoirs uses a continuous mixing process, which has high requirements on the swelling rate of the thickener. The current common practice is to pretreat the polymer thickener so that its molecular chain can be pre-stretched, shortening the dispersion time in water during continuous mixing and ensuring the smooth progress of the continuous mixing construction.

[0003] At present, the high surface area of ​​clay is used to compound the corresponding surfactant to suspend the polymer thickener in the oil phase to improve the stretching ability of the polymer. However, the use of clay increases the solid content entering the well, which will cause certain blockage of the pore throat after the transformation and reduce the effect after compression.

[0004] Nano-silica has a large surface area and can be used as a suspending agent. In addition, nano-silica has a small particle size. After entering the formation, it can reduce the interaction between crude oil and rock and provide power for the flow of crude oil. Nano-silica is widely used in the field of oilfield development. However, in the suspension process of polymer compounds, since conventional nano-silica is hydrophilic, it cannot be well dispersed in the oil phase; after surface modification with silane groups, the hydrophilicity of nano-silica is weakened, but the silane groups used have a hydrophilic group, so that the modified nano-silica still has a certain hydrophilicity, and the dispersion stability in oil is relatively poor, and the stability time is basically short.

[0005] Although nano-silica has a certain promoting effect on improving the performance of fracturing fluid and increasing crude oil recovery after surface functionalization chemical modification, the large number of silanol groups on the surface of nano-silica present strong negative charge, making it difficult to form a stable suspension system with oil, limiting the application of nano-silica in fracturing fluid. For this reason, it is necessary to modify the surface of nano-silica to improve the dispersibility of the material to meet the requirements of oil field use. Liu Peisong et al. used modifiers to modify the surface of nano-silica to change its surface negative charge, and used polymers, surfactants, etc. to coat the surface of nano-silica, compounding it into a quaternary composite oil displacement system based on hydrophobicity controllable nano-silica that is stably dispersed under reservoir conditions.

[0006] The Chinese patent document with publication number CN114574185A discloses a quaternary composite oil displacement system based on hydrophobicity controllable nano-silicon dioxide and its preparation method. This method for improving the dispersibility of nano-silicon dioxide does not take into account the balance between the hydrophobic group and the hydrophilic group of nano-silicon dioxide, and the effect is still poor when compounded with other compounds. The Chinese patent document with publication number CN112175208A discloses a polymer suspension emulsion for fracturing fluid and its preparation method, which adopts carboxymethyl cellulose, bentonite, and a mixture of the two as a suspending agent to prepare a polymer suspension emulsion for fracturing fluid. Although this polymer suspension emulsion can meet the requirements of dispersion stability and continuous mixing of the emulsion, the emulsion system introduces bentonite, increases the solid content of the well, and causes certain blockage to the pore throat after the transformation, reducing the reservoir transformation effect. Summary of the invention

[0007] The present invention provides a modified nano-silicon dioxide continuously mixed fracturing fluid, which overcomes the shortcomings of the above-mentioned prior art and can effectively solve the problems of long fluid preparation time, high labor intensity, residual fluid pollution of the environment, low degree of automation, and failure to meet the "large fluid volume and large displacement" requirements of factory-based construction in conventional fracturing operations of "prepare fluid before construction".

[0008] One of the technical solutions of the present invention is achieved through the following measures: a modified nano-silica continuously mixed fracturing fluid, the raw materials of which include, by mass percentage: 2% to 6% of hydrophobicity controllable nano-silica, 0.5% to 1.2% of surface treatment agent, 30% to 48% of polyacrylamide, and 44.8% to 67.5% of base oil.

[0009] The following are further optimizations and / or improvements to the above technical solutions: The surface treatment agent is a nonionic surfactant of a block copolymer of polyoxyethylene ether and polyoxypropylene ether.

[0010] The polyacrylamide is a cationic polyacrylamide or anionic polyacrylamide with a molecular weight of 6 million to 12 million and a particle size of 150 mesh to 200 mesh.

[0011] The base oil is one or more of 5#, 10# and 15# white oil.

[0012] The above-mentioned hydrophobicity controllable nano-silicon dioxide has a particle size of 30nm to 50nm and is prepared according to the following steps: The first step is to add a required amount of nano-silicon dioxide prepared by hydrolysis precipitation method and cyclohexane into the first reactor, and disperse by ultrasonic to obtain a nano-silicon dioxide mixed solution; The second step is to add the required amount of cyclohexane, hydrophobic modifier and hydrophilic modifier into the second reactor, seal the second reactor, and stir at room temperature to obtain a modifier mixed solution; The third step is to add hydrochloric acid to the first reactor at the desired temperature to adjust the pH of the nano-silica mixed solution to 4.5 to 5, add the modifier mixed solution to the first reactor, stir the reaction for 10 to 15 hours, and the reaction product is centrifuged, washed, dried, and ground to obtain nano-silica with controllable hydrophobicity.

[0013] In the first step, the mass ratio of nano-silicon dioxide to cyclohexane is 3 to 5:8 to 9. In the second step, the mass ratio of the total mass of the hydrophobic modifier and the hydrophilic modifier to cyclohexane is 2 to 8:20 to 30.

[0014] The hydrophobic modifier is trimethoxy(pentyl)silane or trimethoxy(hexyl)silane, and the hydrophilic modifier is 1-amino-5-(trimethoxysilyl)pentane-2-ol or 1-amino-6-(trimethoxysilyl)hexane-2-ol.

[0015] The mass ratio of the hydrophobic modifier, the hydrophilic modifier and the nano-silica is 3 to 6:1:30 to 60.

[0016] The modified nano-silica continuously mixed fracturing fluid is prepared according to the following steps: adding base oil into a reactor, starting a stirrer, adding hydrophobicity-controllable nano-silica, adding a surface treatment agent until the hydrophobicity-controllable nano-silica is completely dispersed, and then continuously adding polyacrylamide into the reactor, stirring for 30 minutes to 1 hour to obtain the modified nano-silica continuously mixed fracturing fluid.

[0017] The second technical solution of the present invention is achieved by the following measures: a method for preparing a modified nano-silica continuously mixed fracturing fluid, which is carried out according to the following steps: adding base oil to a reactor, starting a stirrer, adding hydrophobicity-controllable nano-silica, adding a surface treatment agent after the hydrophobicity-controllable nano-silica is completely dispersed, and then continuously adding polyacrylamide to the reactor, stirring for 30 minutes to 1 hour, and obtaining a modified nano-silica continuously mixed fracturing fluid.

[0018] The third technical solution of the present invention is achieved through the following measures: a method for using a modified nano-silicon dioxide continuously mixed fracturing fluid, which is carried out according to the following steps: adding water to a reactor, starting an agitator, adding the modified nano-silicon dioxide continuously mixed fracturing fluid, until the liquid is completely dissolved, and adjusting the amount of the modified nano-silicon dioxide continuously mixed fracturing fluid according to the type of fracturing fluid to achieve the required viscosity of the fracturing fluid, thereby realizing integrated continuous mixing construction.

[0019] The present invention provides a modified nano-silicon dioxide continuously mixed fracturing fluid, which is easy to operate in its preparation and use methods, has the characteristics of low damage and continuous mixing, can effectively improve the stability of the oil phase dispersed polymer compound system, and realizes rapid swelling of the fracturing fluid system and immediate use after preparation, which can reduce the preparation time in fracturing operations, improve the degree of automation, reduce labor intensity, and avoid residual liquid pollution. DETAILED DESCRIPTION

[0020] The present invention is not limited by the following embodiments, and the specific implementation method can be determined according to the technical scheme of the present invention and the actual situation. Unless otherwise specified, the various chemical reagents and chemicals mentioned in the present invention are all known and commonly used chemical reagents and chemicals in the prior art; unless otherwise specified, the percentages in the present invention are all mass percentages; the normal temperature and room temperature in the present invention generally refer to the temperature of 15°C to 25°C, and are generally defined as 25°C.

[0021] The present invention will be further described below in conjunction with embodiments: Example 1: The modified nano-silica is continuously mixed with a fracturing fluid, and the raw materials include, by mass percentage: 2% to 6% of nano-silica with controllable hydrophobicity, 0.5% to 1.2% of a surface treatment agent, 30% to 48% of polyacrylamide, and 44.8% to 67.5% of a base oil.

[0022] Example 2: As an optimization of the above example, the surface treatment agent is a nonionic surfactant of a block copolymer of polyoxyethylene ether and polyoxypropylene ether. This surface treatment agent has polyoxypropylene ether as a hydrophobic group and polyoxyethylene ether as a hydrophilic group, and has the following structure: .

[0023] Embodiment 3: As an optimization of the above embodiment, the polyacrylamide is a cationic polyacrylamide or anionic polyacrylamide with a molecular weight of 6 million to 12 million and a particle size of 150 mesh to 200 mesh.

[0024] Example 4: As an optimization of the above example, the base oil is one or more of 5#, 10# and 15# white oils.

[0025] Example 5: As an optimization of the above example, the hydrophobicity-controllable nano-silicon dioxide particle size is 30 nm to 50 nm and is prepared according to the following steps: The first step is to add a required amount of nano-silicon dioxide prepared by hydrolysis precipitation method and cyclohexane into the first reactor, and disperse by ultrasonic to obtain a nano-silicon dioxide mixed solution; The second step is to add the required amount of cyclohexane, hydrophobic modifier and hydrophilic modifier into the second reactor, seal the second reactor, and stir at room temperature to obtain a modifier mixed solution; The third step is to add hydrochloric acid to the first reactor at the desired temperature to adjust the pH of the nano-silica mixed solution to 4.5 to 5, add the modifier mixed solution to the first reactor, stir the reaction for 10 to 15 hours, and the reaction product is centrifuged, washed, dried, and ground to obtain nano-silica with controllable hydrophobicity.

[0026] Example 6: As an optimization of the above example, in the first step, the mass ratio of nano-silica to cyclohexane is 3 to 5:8 to 9, and in the second step, the mass ratio of the total mass of the hydrophobic modifier and the hydrophilic modifier to cyclohexane is 2 to 8:20 to 30.

[0027] Example 7: As an optimization of the above example, the hydrophobic modifier is trimethoxy(pentyl)silane or trimethoxy(hexyl)silane, and the hydrophilic modifier is 1-amino-5-(trimethoxysilyl)pentane-2-ol or 1-amino-6-(trimethoxysilyl)hexane-2-ol.

[0028] Example 8: As an optimization of the above example, the mass ratio of the hydrophobic modifier, the hydrophilic modifier and the nano-silica is 3 to 6:1:30 to 60.

[0029] The nano silicon dioxide obtained by the hydrolysis precipitation method in the present invention contains a large amount of hydroxyls on its surface, which makes it hydrophilic and cannot be stably suspended in the oil phase. A large amount of hydroxyls on the surface of the nano silicon dioxide are consumed by a hydrophobic modifier (trimethoxy (pentyl) silane or trimethoxy (hexyl) silane) to increase the hydrophobicity of silicon dioxide. However, in the field of petroleum, conventional water-soluble macromolecular compounds are used, and these macromolecular compounds containing a large amount of hydrophilic groups are dispersed in the oil phase, and suspending agents can act on these hydrophilic groups. Therefore, in order to utilize nano silicon dioxide to suspend water-soluble macromolecular compounds in the oil phase, the affinity and repellency on the surface of the nano silicon dioxide must be controlled at a balance point, that is, the hydrophobic modifier: hydrophilic modifier: nano silicon dioxide mass ratio is controlled to: 3 to 6:1:30 to 60.

[0030] The present invention adopts nano-silicon dioxide with controllable hydrophobicity as an oil phase suspending agent, avoiding the use of clay that may cause damage to the reservoir. Clay will swell and migrate after encountering water, blocking the tiny pore throats of the reservoir, while nano-silicon dioxide will not change when encountering water, and the used silica particle size is only 30nm to 50nm, which will not affect the pore throats of the reservoir. The surface hydrophobic groups of the nano-silicon dioxide particles with controllable hydrophobicity are relatively large, and the dispersibility in the oil phase is good. The small amount of hydrophilic groups on the surface of the particles can well react with the polymer compound containing the hydrophilic group, thereby improving the suspension ability of the hydrophilic polymer compound.

[0031] Example 9: The preparation method of the modified nano-silica continuously mixed fracturing fluid is carried out according to the following steps: add base oil into the reactor, start the agitator, add hydrophobicity controllable nano-silica, add the surface treatment agent after the hydrophobicity controllable nano-silica is completely dispersed, and then continuously add polyacrylamide into the reactor. After stirring for 30 minutes to 1 hour, the modified nano-silica continuously mixed fracturing fluid is obtained.

[0032] Example 10: The method for using the modified nano-silica continuously mixed fracturing fluid is carried out according to the following steps: add water to the reactor, start the agitator, add the modified nano-silica continuously mixed fracturing fluid, until the liquid is completely dissolved, and adjust the amount of the modified nano-silica continuously mixed fracturing fluid according to the type of fracturing fluid (such as pre-fluid, sand-carrying fluid, displacement fluid) to achieve the required viscosity of the fracturing fluid (i.e., viscosity grading using the modified nano-silica continuously mixed fracturing fluid), thereby realizing integrated continuous mixing construction.

[0033] In the present invention, an enamel liner reactor can be used in the preparation and use of the modified nano-silicon dioxide continuous mixing fracturing fluid.

[0034] Embodiment 11: Add 675kg of 5# white oil to a clean enamel-lined reactor, start the agitator, slowly add 20kg of hydrophobicity-controllable nano-silica (particle size 30nm), add 5kg of polyoxyethylene ether and polyoxypropylene ether block copolymer non-ionic surfactant until the hydrophobicity-controllable nano-silica is completely dispersed, then slowly and continuously add 300kg of cationic polyacrylamide (molecular weight 12 million) into the reactor, and after stirring for 30 minutes, the modified nano-silica continuously mixed fracturing fluid is obtained.

[0035] Embodiment 12: Add 608kg 10# white oil to a clean enamel-lined reactor, start the agitator, slowly add 35kg hydrophobicity-controllable nano-silica (particle size 50nm), until the hydrophobicity-controllable nano-silica is completely dispersed, then add 7kg polyoxyethylene ether and polyoxypropylene ether block copolymer non-ionic surfactant, and then slowly and continuously add 350kg cationic polyacrylamide (molecular weight 12 million) into the reactor. After stirring for 30 minutes, the modified nano-silica continuously mixed fracturing fluid is obtained.

[0036] Embodiment 13: Add 534kg 15# white oil to a clean enameled reactor, start the agitator, slowly add 58kg hydrophobicity controllable nano-silica (particle size 50nm), add 8kg polyoxyethylene ether and polyoxypropylene ether block copolymer non-ionic surfactant until the hydrophobicity controllable nano-silica is completely dispersed, then slowly and continuously add 400kg anionic polyacrylamide (molecular weight 12 million) into the reactor, stir for 30 minutes, and obtain the modified nano-silica continuously mixed fracturing fluid.

[0037] Embodiment 14: Add 220kg 5# white oil and 298kg 15# white oil to a clean enamel-lined reactor, start the agitator, slowly add 52kg hydrophobicity-controllable nano-silica (particle size 30nm), until the hydrophobicity-controllable nano-silica is completely dispersed, then add 10kg polyoxyethylene ether and polyoxypropylene ether block copolymer non-ionic surfactant, and then slowly and continuously add 420kg anionic polyacrylamide (molecular weight 8 million) into the reactor. After stirring for 30 minutes, the modified nano-silica continuously mixed fracturing fluid is obtained.

[0038] Embodiment 15: Add 160kg10# white oil and 288kg15# white oil to a clean enamel-lined reactor, start the agitator to let the oil flow, slowly add 60kg of hydrophobicity-controllable nano-silica (particle size 40nm), until the hydrophobicity-controllable nano-silica is completely dispersed, then add 12kg of polyoxyethylene ether and polyoxypropylene ether block copolymer non-ionic surfactant, and then slowly and continuously add 480kg of anionic polyacrylamide (molecular weight 6 million) into the reactor. After stirring for 30 minutes, the modified nano-silica continuously mixed fracturing fluid is obtained.

[0039] Comparative Example 1: Add 534kg 15# white oil to a clean enameled reactor, start the agitator to let the oil flow, slowly add 58kg modified bentonite (particle size 50nm), until the modified bentonite is completely dispersed, then add 8kg polyoxyethylene ether and polyoxypropylene ether block copolymer non-ionic surfactant, and then slowly and continuously add 400kg anionic polyacrylamide (molecular weight 12 million) into the reactor. After stirring for 30 minutes, the modified bentonite fracturing fluid is obtained.

[0040] The modified nano-silica continuously mixed fracturing fluids prepared in Examples 11 to 15 and the modified bentonite fracturing fluids prepared in Comparative Example 1 were made into 0.5% solutions, and the apparent viscosities at different times were tested using a six-speed viscometer, and their dissolution and thickening properties are shown in Table 1. As can be seen from Table 1, compared with the modified bentonite fracturing fluid, the modified nano-silica continuously mixed fracturing fluid of the present invention has a faster dissolution time, and can achieve rapid swelling within 2 minutes. The addition of nano-silica with controllable hydrophobicity makes the fracturing fluid viscosity higher than that of the modified bentonite fracturing fluid, and the viscosity of the 0.5% solution is greater than 50 mPa·s.

[0041] The present invention provides a low-damage, continuously mixed fracturing fluid system, which uses a hydrophobic nano-silicon dioxide as a suspending agent, reduces the hydrophilic groups on the surface of the nano-silicon dioxide as much as possible, and improves the dispersibility of the nano-silicon dioxide in the oil base. On the other hand, by designing the reserved hydrophilic groups (amino and hydroxyl groups), the nano-silicon dioxide can react with the polymer compound containing a large number of hydrophilic groups, thereby improving the stability of the oil phase dispersed polymer compound system. In addition, in order to give full play to the rapid swelling and ready-to-use functions of the suspended polyacrylamide polymer of the nano-silicon dioxide, an organic oil phase is used as a solvent, the hydrophobic nano-silicon dioxide is used as a suspending agent, and a surfactant is added to improve the suspension stability, and finally a set of continuously mixed hydrophobic nano-silicon dioxide suspended fracturing fluid is formed.

[0042] In summary, the present invention provides a modified nano-silica continuously mixed fracturing fluid, which is easy to operate in its preparation and use methods, has the characteristics of low damage and continuous mixing, can effectively improve the stability of the oil phase dispersed polymer compound system, and realizes rapid swelling of the fracturing fluid system and immediate use after preparation, which can reduce the preparation time in fracturing operations, improve the degree of automation, reduce labor intensity, and avoid residual liquid pollution.

[0043] The above technical features constitute the embodiments of the present invention, which have strong adaptability and implementation effect. Non-essential technical features can be added or reduced according to actual needs to meet the requirements of different situations.

Claims

1. A modified nano-silicon dioxide continuously mixed fracturing fluid, characterized in that The raw materials include, by mass percentage: 2% to 6% of hydrophobicity controllable nano-silicon dioxide, 0.5% to 1.2% of surface treatment agent, 30% to 48% of polyacrylamide, and 44.8% to 67.5% of base oil.

2. The modified nano-silicon dioxide continuously mixed fracturing fluid according to claim 1, characterized in that The surface treatment agent is a nonionic surfactant of a block copolymer of polyoxyethylene ether and polyoxypropylene ether.

3. The modified nano-silicon dioxide continuously mixed fracturing fluid according to claim 1 or 2, characterized in that The polyacrylamide is a cationic polyacrylamide or anionic polyacrylamide with a molecular weight of 6 million to 12 million and a particle size of 150 mesh to 200 mesh.

4. The modified nano-silicon dioxide continuously mixed fracturing fluid according to any one of claims 1 to 3, characterized in that The base oil is one or more of 5#, 10# and 15# white oil.

5. The modified nano-silicon dioxide continuously mixed fracturing fluid according to any one of claims 1 to 4, characterized in that The hydrophobicity-controllable nano-silicon dioxide has a particle size of 30 nm to 50 nm and is prepared according to the following steps: The first step is to add a required amount of nano-silicon dioxide prepared by hydrolysis precipitation method and cyclohexane into the first reactor, and disperse by ultrasonic to obtain a nano-silicon dioxide mixed solution; The second step is to add the required amount of cyclohexane, hydrophobic modifier and hydrophilic modifier into the second reactor, seal the second reactor, and stir at room temperature to obtain a modifier mixed solution; The third step is to add hydrochloric acid to the first reactor at the desired temperature to adjust the pH of the nano-silica mixed solution to 4.5 to 5, add the modifier mixed solution to the first reactor, stir the reaction for 10 to 15 hours, and the reaction product is centrifuged, washed, dried, and ground to obtain nano-silica with controllable hydrophobicity.

6. The modified nano-silicon dioxide continuously mixed fracturing fluid according to claim 5, characterized in that In the first step, the mass ratio of nano-silica to cyclohexane is 3 to 5:8 to 9, and in the second step, the mass ratio of the total mass of the hydrophobic modifier and the hydrophilic modifier to cyclohexane is 2 to 8:20 to 30.

7. The modified nano-silicon dioxide continuously mixed fracturing fluid according to claim 5 or 6, characterized in that The hydrophobic modifier is trimethoxy(pentyl)silane or trimethoxy(hexyl)silane, and the hydrophilic modifier is 1-amino-5-(trimethoxysilyl)pentane-2-ol or 1-amino-6-(trimethoxysilyl)hexane-2-ol; or / and, the mass ratio of the hydrophobic modifier, the hydrophilic modifier and the nano-silica is 3 to 6:1:30 to 60.

8. The modified nano-silicon dioxide continuously mixed fracturing fluid according to any one of claims 1 to 7, characterized in that The preparation is carried out according to the following steps: adding base oil into a reactor, starting a stirrer, adding hydrophobicity-controllable nano-silica, adding a surface treatment agent after the hydrophobicity-controllable nano-silica is completely dispersed, and then continuously adding polyacrylamide into the reactor, stirring for 30 minutes to 1 hour, thereby obtaining a modified nano-silica continuously mixed fracturing fluid.

9. A method for preparing a modified nano-silicon dioxide continuously mixed fracturing fluid according to any one of claims 1 to 7, characterized in that The following steps are followed: add base oil into the reactor, start the agitator, add hydrophobicity-controllable nano-silica, add the surface treatment agent after the hydrophobicity-controllable nano-silica is completely dispersed, and then continuously add polyacrylamide into the reactor. After stirring for 30 minutes to 1 hour, the modified nano-silica continuously mixed fracturing fluid is obtained.

10. A method for using the modified nano-silicon dioxide continuously mixed fracturing fluid according to any one of claims 1 to 8, characterized in that Proceed as follows: add water to the reactor, start the agitator, add modified nano-silicon dioxide to continuously mix the fracturing fluid until the liquid is completely dissolved, and adjust the amount of modified nano-silicon dioxide to continuously mix the fracturing fluid according to the type of fracturing fluid to achieve the required viscosity of the fracturing fluid, thereby realizing integrated continuous mixing construction.

Citation Information

Patent Citations

  • Polymer suspension emulsion for fracturing fluid and preparation method thereof

    CN112175208A

  • Quaternary composite oil displacement system based on modified nano silicon dioxide and preparation method of quaternary composite oil displacement system

    CN114574185A